The Role of Islamic Education to Overcome Drugs Abuse in The Family - Aliandi Lumbu; Ahmad Mukhlisin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2019)
Teenagers are children in unstable times that are full of potential with high curiosity. With a very high curiosity but a little knowledge and experience so often teens try new things without thinking about the impact that will be faced for themselves and for others. At this time, parents must approach the adolescents and be followed by moral and faith planting so that teens can be well directed. This qualitative research aims to describe the application of Islamic religious education in dealing with juvenile delinquency. Especially for prevention of drug use that has entered urban areas and settlements, especially in Kampung V Kampung Purwodadi Trimurjo, Central Lampung. In the end, this study found that creating an Islamic family environment will foster adolescents who are virtuous and religious who avoid drug abuse.